1 Efektifitas Intradialytic Stretching Exercise Terhadap Penurunan Gejala Restless Leg Syndrome Dan Peningkatan Sleep Quality Pada Pasien Hemodialisis Tahun 2018 - Achmad Fauzi (UP3M AKPER-AKBID BHAKTI HUSADA CIKARANG, 2019)
Introduction : Chronic Kidney Disease (CKD) is one of the major diseases in the world, affecting the huge medical, economic and social problems for patients and their families. The necessary intervention is renal replacement therapy that is hemodialysis. Hemodialysis is a lifetime therapy with the frequency of action every 2-3 times / week and the required duration is 4-6 hours in every one hemodialysis session. Changes are often complained in patients undergoing hemodialysis that is restless leg syndrome and decreased sleep quality. To overcome these symptoms are done intradialytic stretching exercise. Method : The design of this study used two groups of Pre post-test design with T dependent test data analysis for bivariate data, and frequency distribution for univariate data before and after intradialytic stretching exercise. Symptom score Restless leg syndrome was tested using IRLSG instrument and sleep quality score tested using PQSI Scale. Result : There were 19 patients with symptoms of restless leg syndrome and sleep quality disorder. After intervention, RLS and sleep quality decrease by 1.32 with pvalue <0.00. Conclusion : It can be concluded that Intradialytic stretching exercise is effective in reducing RLS symptoms and improving sleep quality.